2021
DOI: 10.1186/s13071-021-04691-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of tropisetron and granisetron against Echinococcus granulosus (s.s.) protoscoleces by involvement of calcineurin and calmodulin

Abstract: Background Cystic echinococcosis (CE) is a disease caused by the larval stage of Echinococcus granulosus sensu lato  (s.l.). The treatment of CE mainly relies on the use of benzimidazoles, which can commonly cause adverse side effects. Therefore, more efficient treatment options are needed. Drug repurposing is a useful approach for advancing drug development. We have evaluated the in vitro protoscolicidal effects of tropisetron and granisetron in E. granulosus sensu stricto (s.s.) and assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…5-HT3R antagonists, including ondansetron, tropisetron, and granisetron, are primarily used to avert nausea and vomiting after chemotherapy and radiation. Experimental studies showed diverse positive effects of these agents, e.g., anti-depressant effects of ondansetron and tropisetron in rodents [32], diminution of colitis-associated cancer by tropisetron in mice [33], anti-inflammatory and anti-oxidant properties of tropisetron in early diabetic nephropathy of rats [34], suppression of vincristine-induced neuropathy by tropisetron in rats [35], and parasiticidal effects of tropisetron and granisetron against Echinococcus granulosus in-vitro [36]. Ondansetron and tropisetron are 5-HT3R antagonists with various distributions in CNS.…”
Section: Discussionmentioning
confidence: 99%
“…5-HT3R antagonists, including ondansetron, tropisetron, and granisetron, are primarily used to avert nausea and vomiting after chemotherapy and radiation. Experimental studies showed diverse positive effects of these agents, e.g., anti-depressant effects of ondansetron and tropisetron in rodents [32], diminution of colitis-associated cancer by tropisetron in mice [33], anti-inflammatory and anti-oxidant properties of tropisetron in early diabetic nephropathy of rats [34], suppression of vincristine-induced neuropathy by tropisetron in rats [35], and parasiticidal effects of tropisetron and granisetron against Echinococcus granulosus in-vitro [36]. Ondansetron and tropisetron are 5-HT3R antagonists with various distributions in CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Both tropisetron and granisetron have dose-dependent protoscolecidal activity, much more so in the case of tropisetron, possibly because of its additional mode of action. Furthermore, tropisetron was more effective than albendazole sulfoxide at the concentrations tested [14 ▪▪ ]. A clinical trial of tropisetron pre and post PAIR or operative surgery should be considered.…”
Section: Repurposing Existing Drugs For Cystic Echinococcosis?mentioning
confidence: 92%